2014
DOI: 10.1590/s0080-623420140000800014
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Disease in the Elderly: Spirituality and Coping

Abstract: This is an exploratory study using a qualitative methodology which aimed to identify and understand the role of spirituality in the management of chronic disease in the elderly. The discourse analysis revealed the following central themes: multidimensional impact of chronic diseases, coping and expectations of the elderly. Regarding coping with chronic diseases, the individual coping, social support and religiosity/spirituality/faith were analyzed. The results showed the changes brought about the diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 21 publications
2
24
1
7
Order By: Relevance
“…These tools are a form of living communication between the devotee and a God, imagined as personal and experienced as present. This communication reflects the form of social human relationships (22)(23) .…”
Section: Discussionmentioning
confidence: 98%
“…These tools are a form of living communication between the devotee and a God, imagined as personal and experienced as present. This communication reflects the form of social human relationships (22)(23) .…”
Section: Discussionmentioning
confidence: 98%
“…Another possibility is that more experienced caregivers can provide a resilient care, a fact that might be a new aspect to be studied. A 2014 study shows the resilience of the older adult as a result of the inconveniences and difficulties experienced during the trajectory of their lives, making them more fit to deal with critical moments 31 . …”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that many individuals rely on their spirituality and faith when coping with stres in most cultures. (16)(17)(18)(19)(20) Dedeli & Kaptan (13) indicated that people apply cognitive and behavioral strategies including religion/spirituality to cope with pain. Another study showed religious-spiritual coping can be very helpful when dealing with chronic disease.…”
Section: Dıscussıonmentioning
confidence: 99%